Concert and Charity: Operating Da’wah Activism through Maher Zain’s Pop Culture Industry - Fairuz, Rifqi (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Maher Zain is an icon of Islamic pop culture with the largest market share in the world. Indonesia constitutes the largest Maher Zain's fan base with multiple platinum awards and recorded million copies of album sale. Maher Zain's rise to fame coincided with the shifting of conventional Islamic authority, which turned from Kiai or Ulama to popular Muslim preachers. These preachers seek aspirations of Islamism in social and political movements through the da’wah institutions they lead. This article is aimed to examine the intersection between the Islamic pop culture industry, Maher Zain as a leading Muslim singer icon, and the strategies of Islamic activism of da’wah in Indonesia. This research found that popular preachers utilize their charitable activities, philanthropy and Islamic da'wah to legitimize and capitalize on Maher Zain's popularity in Indonesia, by playing role in the capitalistic mechanism of the Islamic music industry. These da'wah institutions operate through industrial mechanisms for the benefit of Islamic da'wah activism in Indonesia and even become an advantage in the midst of the struggle for political Islam in Indonesia.